Enterprise interoperability : 6th International IFIP Working Conference, IWEI 2015, Nîmes, France, May 28-29, 2015, Proceedings /: 6th International IFIP Working Conference, IWEI 2015, Nîmes, France, May 28-29, 2015, Proceedings. (2015) - Unknown
No abstract available